IMPROVING STUDENTS’ SPEAKING SKILL THROUGH PEER TUTORING IN SMP MUHAMMADIYAH BOARDING SCHOOL TARAKAN - Anita, Lisdiana (Borneo Journal of English Language Education, 2023)
ABSTRACTThis research is aimed at discovering the improvement of students’ speaking skill by implementing the method of peer tutoring. The research was conducted on first grade students of SMP Muhammadiyah Boarding School Tarakan.  The researcher used Classroom Action Research with two cycles to observe the improvement of students’ speaking skill. The two cycles included planning, acting, observing, and reflecting. The research used descriptive qualitative method. Then, the data collection methods were observation, questionnaires, and tests. The result of this research showed that the students’ speaking skill were improved through the implementation of peer tutoring method. Students’ speaking score was increased from the pre-test, cycle 1, to cycle 2. It increased 7.0 points from cycle 1 to cycle 2. Besides, the students became more active and confidence than before. The result of this research confirmed that the method of peer tutoring could improve the students’ speaking skill at the first grade students of SMP Muhammadiyah Boarding School Tarakan.Keywords: Peer tutoring, speaking